Relationship between immediate auditory memory and spelling learning difficulties in children of fifth and sixth grade of elementary education in public and private schools in Lima Metropolitana - Dioses Chocano, Alejandro (2003)
The objective of the present study was to establish if a significant relation between the yield in immediate auditory memory and the difficulties in the learning of the spelling in students existed who attended the fifth and sixth degree of primary education in schools Metropolitan deprived public and of Lima. The investigated subjects were students of 5° and 6° primary degree of different socioeconomic level, whose ages fluctuated between the 9 and 12 years, becoming use of the descriptive method with correlational design. The data collection took place with the Test of immediate Auditory Memory and the Test of Orthographic Yield. The results as much showed that the students of private schools presented/displayed a better orthographic performance with respect to the students of schools public and who, in the students of schools public, like in those of deprived schools, the orthographic number of errors diminishes progressively in agreement is progressed in age and scholastic degree, finally verified that a significant and inverse relation between the immediate auditory memory exists and the amount of orthographic errors committed.